Infraspinatus muscle necrosis in a cat with primary hyperaldosteronism - Go Otani; Hiroshi Ohta (Journal of Feline Medicine and Surgery Open Reports)
Case summary Persistent and progressive weakness secondary to hypokalaemia, that is, hypokalaemic polymyopathy, is one of the most common clinical signs of primary hyperaldosteronism (PHA). Herein, we report a case of PHA with infraspinatus muscle necrosis. A 5-year-old castrated male domestic shorthair cat presented with a history of polyuria and polydipsia, decreased activity, staggering gait, difficulty in jumping and inward rotation of both forelimbs. Blood examination revealed hypokalaemia, increased serum creatinine kinase activity and high serum aldosterone concentration. Abdominal ultrasonography and CT revealed an enlarged right adrenal gland. Post-contrast thoracic CT showed peripheral contrast enhancement and a non-enhanced centre in the bilateral infraspinatus muscles. From the day of initial presentation, the cat was started on oral potassium replacement therapy. On day 17, the right adrenal gland was surgically resected and the left infraspinatus muscle was biopsied. Histopathological examination confirmed the presence of an adrenocortical adenoma in the right adrenal gland and necrosis of the muscle fibres in the left infraspinatus muscle. On day 29, all clinical signs had disappeared, and the serum potassium concentration, creatinine kinase activity and aldosterone concentration had normalised. On day 57, atrophy of the bilateral infraspinatus muscles was noted, but there was no evidence of any posture or gait abnormalities. Relevance and novel information To the authors’ knowledge, this is the first report of possible infraspinatus muscle necrosis in a cat with PHA. It is also possible that the infrinatus muscle necrosis with hypokalaemic polymyopathy secondary to PHA was caused by compartment syndrome in the cat described here.